2019
DOI: 10.1007/s00709-018-01340-4
|View full text |Cite
|
Sign up to set email alerts
|

Triterpenoid gene expression and phytochemical content in Iranian licorice under salinity stress

Abstract: Licorice is a well-known medicinal plant, containing various secondary metabolites of triterpenoid and phenolic families. The aim of this study is to evaluate the effect of salinity stress on the expression of key genes involved in the biosynthetic pathway of triterpenoids such as glycyrrhizin, betulinic acid, soyasaponins, and phytosterols in licorice root, as well as providing a phonemic platform to characterize antioxidant properties, glycyrrhizin, and total phenolic content. This study also includes measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“… Behdad et al (2020) found that 100 mM NaCl significantly upregulated the expression level of key genes (β -AS , CYP88D6 , and CYP72A154 ) in Glycyrrhiza glabra L. involved in triterpenoid saponin biosynthesis and directly increased the content of glycyrrhizic acid. Shirazi et al (2019) also found that salt stress upregulated the expression level of key genes (including SQS , β -AS , LUS , CAS , CYP88D6 , and CYP93E6 ) in Iranian licorice. Moreover, Wang et al (2020) reported that 200 mM NaCl upregulated the expression level of key enzymes (β-AS, CYP88D6, and CYP72A154) involved in the glycyrrhizic acid biosynthesis pathway in G. uralensis .…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“… Behdad et al (2020) found that 100 mM NaCl significantly upregulated the expression level of key genes (β -AS , CYP88D6 , and CYP72A154 ) in Glycyrrhiza glabra L. involved in triterpenoid saponin biosynthesis and directly increased the content of glycyrrhizic acid. Shirazi et al (2019) also found that salt stress upregulated the expression level of key genes (including SQS , β -AS , LUS , CAS , CYP88D6 , and CYP93E6 ) in Iranian licorice. Moreover, Wang et al (2020) reported that 200 mM NaCl upregulated the expression level of key enzymes (β-AS, CYP88D6, and CYP72A154) involved in the glycyrrhizic acid biosynthesis pathway in G. uralensis .…”
Section: Discussionmentioning
confidence: 80%
“…The content of compounds and the expression level of key genes have significantly changed in glycyrrhizic acid and liquiritin biosynthesis pathway during abiotic stress, salt stress specifically caught our attention ( Wang et al, 2015 , 2017 ; Zhou et al, 2017 ; Yeo et al, 2018 ; Kaur and Ganjewala, 2019 ). Shirazi et al (2019) reported that salt stress significantly upregulated the expression level of SQS , β -AS , CAS , LUS , and some CYPs genes and increased the content of glycyrrhizin in Glycyrrhiza glabra , which illustrated that salt stress inhibited in the glycyrrhizin biosynthesis pathway. In conclusion, we provided a basis for further studies concerned with the relation between salt stress and glycyrrhizic acid pathway and liquiritin pathway in G. uralensis .…”
Section: Introductionmentioning
confidence: 95%
“…SMRGs including MYB15 ( Marchev et al, 2020 ), NAC29 ( Huang et al, 2015 ; Wang T. T. et al, 2019 ), TLP3 ( Ibrahim and Jaafar, 2013 ; Bao et al, 2014 ), HFB2A ( Paupiere et al, 2020 ), WRKY27 , OLE16 ( Shao et al, 2019 ), BBE8 ( Daniel et al, 2017 ), LEA3 ( Zhao et al, 2011 ), CHSY ( Dao et al, 2011 ), DRE1D ( Agarwal et al, 2017 ), Malate synthase ( de Kraker and Gershenzon, 2011 ), cycloartenol synthase ( Jin et al, 2017 ) and CASL1 ( Taura et al, 2007 ) in drought enhances secondary metabolite responsive pathways and exert to provide tolerance in the adverse condition in drought stress condition. In salt, several identified genes such as TLP ( Zare-Hassani et al, 2019 ; de Jesus-Pires et al, 2020 ), WRKY6 ( Robatzek and Somssich, 2001 ; Afrin et al, 2015 ), MMP-2 ( Guo et al, 2019 ), peroxidase 53 ( Novo-Uzal et al, 2014 ), bHLH25 ( Goossens et al, 2019 ; Meraj et al, 2020 ; Yang et al, 2020 ), malate synthase ( Brito et al, 2020 ), carboxylesterase ( Wang et al, 2015 ; Cao et al, 2019 ), 1-deoxy-D-xylulose-5-phosphate synthase 2 ( Paetzold et al, 2010 ), NAC ( He et al, 2019 ), DCS2 ( George et al, 2017 ), XTH ( Choi et al, 2011 ; Guerriero et al, 2018 ), AtHB-7 ( Olsson et al, 2004 ), NCED5 ( Udomchalothorn et al, 2017 ), CAS ( Shirazi et al, 2019 ), ERF ( Meraj et al, 2020 ), galactinol synthase ( Patel et al, 2020 ), EXPA7 ( Jadamba et al, 2020 ) and glutathione S-transferase ( Nazar et al, 2011 ; Czerniawski and Bednarek, 2018 ) are SMRGs exhibited crucial role in providing resistance under salt stress condition. Overall, these putative hub genes might have putative functions in drought and salt stress responses in cotton.…”
Section: Discussionmentioning
confidence: 99%
“…Cycloartenol synthase (CAS) converts 2,3-oxidosqualene to cycloartenol through the protosteryl cation intermediate, and was the basal plant OSC from which others derived ( Phillips et al, 2006 ). Some studies have shown that abiotic stress can up-regulate the CAS genes ( Babiychuk et al, 2008 ; Shirazi et al, 2019 ). However, some studies reported no significant change in CAS expression under drought and salt stress ( Basyuni et al, 2009 ; Nasrollahi et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%